PERAN KEPOLISIAN DALAM PENANGANAN TINDAK PIDANA PENCUCIAN UANG (Studi di Kepolisian Daerah Sumatera Utara) - Antonyus Hutahayan; Maidin Gultom; Muhammad Ansori Lubis (JURNAL PROINTEGRITA, 2021)
This research aims at finding the role of the police in dealing with money laundering crime; the role of the police in solving money laundering crimes. Collecting instructions in this research was done by means of field studies and literature studies. Field studies are using the interview method, while literature study obtained principles, conceptions, views, legal doctrine and content of legal principles obtained from two main libraries, namely those that are general (Legislation, Regulations, Textbooks, Dictionaries) and those that are specific (journals, research reports, etc.) The modus operandi of the crime of money laundering is to keep secret who is the real owner and source of the money resulting from the mistake, changing its shape so that it makes tracking difficult by legal officials, so that young people are supervised by the real owner of the wealth (perpetrators of the crime). The role of the North Sumatra Regional Police (Polda) in preventing and overcoming the criminal act of money laundering, at the North Sumatra Regional Police (Polda), there are efforts that can be made, including: Pre-entative measures; Preventive Efforts; Repressive Efforts. In Handling the crime of money laundering, the North Sumatra regional police (Polda) coordinated with Financial Service Providers (PJK), Bank Indonesia, and the Financial Transaction Analysis Reporting Center (PPATK), Information from the Financial Intelligence Units (FIU) of other countries. Inhibiting factors for the North Sumatra Regional Police (Polda) in resolving money laundering crimes include: Factors covering the quantity factor of law enforcement, law enforcement that is less professional. Limited ability to place oneself in the role of the other party with whom he interacts; The level of aspiration is not high enough; Very limited excitement to think about the future, making it very difficult to make a projection; the absence of the ability to postpone the fulfillment of a particular need, especially material; This lack of innovativeness is actually a counterpart to conservatism.